NHS England rushes to hide software over AI hacking fears. - Sparkes, Matthew (New Scientist, 2026)
The article focuses on NHS England’s new policy requiring software created with public funds to be kept private rather than open-source, citing security concerns related to advanced AI models like Anthropic’s Mythos, which reportedly can identify software vulnerabilities. This policy reverses previous NHS rules that mandated public availability of such software to promote reuse and efficiency. However, the UK government-backed AI Security Institute found Mythos poses a threat only to weak systems, and experts argue that open-source software is generally more secure due to public scrutiny. NHS England states the restriction is temporary while assessing AI’s impact and that source code will still be published when clearly necessary.